Unleashing the power of complement activation: unraveling renal damage in human anti-glomerular basement membrane disease - Tang, Anqi; Zhao, Xin; Tao, Tian; Xie, Dengpiao; Xu, Bojun; Huang, Youqun; Li, Mingquan (Frontiers in Immunology, 2023)
Anti-glomerular basement membrane (GBM) disease is a rare but lifethreatening autoimmune disorder characterized by rapidly progressive glomerulonephritis with or without pulmonary hemorrhage. Renal biopsies of anti-GBM patients predominantly show linear deposition of IgG and complement component 3 (C3), indicating a close association between antigen-antibody reactions and subsequent complement activation in the pathogenesis of the disease. All three major pathways of complement activation, including the classical, lectin, and alternative pathways, are involved in human anti-GBM disease. Several complement factors, such as C3, C5b-9, and factor B, show a positive correlation with the severity of the renal injury and act as risk factors for renal outcomes. Furthermore, compared to patients with single positivity for anti-GBM antibodies, individuals who are doubleseropositive for anti-neutrophil cytoplasmic antibody (ANCA) and anti-GBM antibodies exhibit a unique clinical phenotype that lies between ANCA-associated vasculitis (AAV) and anti-GBM disease. Complement activation may serve as a potential "bridge" for triggering both AAV and anti-GBM conditions. The aim of this article is to provide a comprehensive review of the latest clinical evidence regarding the role of complement activation in anti-GBM disease. Furthermore, potential therapeutic strategies targeting complement components and associated precautions are discussed, to establish a theoretical basis for complement-targeted therapies.